IMPLEMENTATION OF MULTICULTURAL EDUCATION TO IMPROVE TOLERANCE ATTITUDE BETWEEN SOCIAL GROUPS IN KALIPURO DISTRICT - Arie Ramadhani; Ramadhan Eri Lugaswara (International Jurnal of Education Schoolars, 2022)
Multicultural education is the process of developing all human potentials that respect plurality and heterogeneity as a consequence of cultural, ethnic, ethnic, and religious diversity. In its implementation, Multicultural Education emphasizes a philosophy of cultural pluralism into the education system which is based on the principles of equality, mutual respect and acceptance and understanding and a moral commitment to social justice. The purpose of this paper is to determine the role and influence of multicultural education in Civics subjects in terms of overcoming the regenerating feud in the Gombeng group and the Madura group. The type of writing used is descriptive qualitative writing. The subjects in this paper are the Gombeng group and the Madura group. The place of writing is done in Kalipuro District, Banyuwangi Regency. In addition, the data collection techniques used are observation, interview and documentation techniques.does not play a role and has a lot of influence to stop the dispute